The Molecular Mechanism of Ginsenoside Analogs Activating TMEM16A - Guo, Shuai; Chen, Yafei F.; Shi, Sai; Pang, Chunli L.; Wang, Xuzhao Z.; Zhang, Hailin L.; Zhan, Yong; An, Hailong L. (Biophysical journal, 2020)
The calcium-activated chloride channel TMEM16A is involved in many physiological processes, and insufficient function of TMEM16A may lead to the occurrence of various diseases. Therefore, TMEM16A activators are supposed to be potentially useful for treatment of TMEM16A downregulation-inducing diseases. However, the TMEM16A activators are relatively rare, and the underlying activation mechanism of them is unclear. In the previous work, we have proved that ginsenoside Rb1 is a TMEM16A activator. In this work, we explored the activation mechanism of ginsenoside analogs on TMEM16A through analyzing the interactions between six ginsenoside analogs and TMEM16A. We identified GRg2 and GRf can directly activate TMEM16A by screening five novel ginsenosids analogs (GRb2, GRf, GRg2, GRh2, and NGR1). Isolated guinea pig ileum assay showed both GRg2 and GRf increased the amplitude and frequency of ileum contractions. We explored the molecular mechanisms of ginsenosides activating TMEM16A by combining molecular simulation with electrophysiological experiments. We proposed a TMEM16A activation process model based on the results, in which A697 on TM7 and L746 on TM8 bind to the isobutenyl of ginsenosides through hydrophobic interaction to fix the spatial location of ginsenosides. N650 on TM6 and E705 on TM7 bind to ginsenosides through electrostatic interaction, which causes the inner half of α-helix 6 to form physical contact with ginsenosides and leads to the pore opening. It should be emphasized that TMEM16A can be activated by ginsenosides only when both the above two conditions are satisfied. This is the first, to our knowledge, report of TMEM16A opening process activated by small-molecule activators. The mechanism of ginsenosides activating TMEM16A will provide important clues for TMEM16A gating mechanism and for new TMEM16A activators screening.